術前栄養状態と心大血管手術後リハビリテーション進行の関連 - 櫻田 弘治; 高橋 哲也; 花房 祐輔; 熊丸 めぐみ; 齊藤 正和; 大浦 啓輔; 湯口 聡; 田原 将之; 上坂 建太; 森沢 知之 (理学療法学, 2013)
Purpose: The purpose of this study is to determine the relationship between the preoperative nutrition state and the progression of rehabilitation after cardiovascular surgery. Methods: Consecutive 479 patients who underwent an elective cardiovascular surgery (male: 317, female: 162, age: 67 ± 13 years old) were recruited. The patients were classified into four groups according to the severity of preoperative GNRI; Geriatric Nutritional Risk Index. We retrospectively examined the relationship between the severity of preoperative GNRI and the progression of postoperative rehabilitation (the postoperative duration until the patient started sitting, standing, walking and completed 100-m walking without assistance). In addition, we examined whether the severity of preoperative GNRI would become a predictive factor of the delay of progression of postoperative rehabilitation. Results: The high-risk group in preoperative GNRI showed a significantly higher ratio of patients with chronic heart failure compared with other groups (p <0.05). Moreover, the high-risk group in preoperative GNRI was delayed in the start of standing-up and walking (p <0.05), and also showed a significantly higher ratio of the delay of progression of postoperative rehabilitation (p < 0.05). The preoperative GNRI was extracted as one of the predicted factors of the progression of postoperative rehabilitation (p <0.001). Conclusion: The preoperative GNRI has a relation to postoperative progression of rehabilitation after cardiovascular surgery. 【目的】術前栄養状態と心大血管手術後のリハビリテーション進行の関連を検討すること。【方法】待機的に心大血管手術を施行した連続479例(男性:317例,女性:162例,年齢:67±13歳)を対象とした。術前Geriatric Nutritional Risk Index(以下,GNRI)を重症度リスクとして4群に分類し,術後リハビリテーション進行(座位・起立・歩行開始病日)や自立歩行遅延との関係を後方視的に調査した。さらに,術前GNRIが心大血管手術後の自立歩行遅延の予測因子となるか検討した。【結果】術前GNRI重度リスク群は他のすべての群に比べて慢性心不全の患者の割合が有意に多かった(p<0.05)。また術前GNRI重度リスク群は,起立開始病日と歩行開始病日が遅延し(p<0.05),さらに自立歩行遅延例の割合も有意に多かった(p<0.05)。心大血管手術後の自立歩行遅延の規定因子のひとつとして術前GNRI(p<0.0001)が抽出された。【結論】術前GNRIは心臓血管手術後のリハビリテーション進行と関連がある。